Marital commitment as a function of marital satisfaction, marital investment and marital alternatives among working women in Malaysia - Juhari, Rumaya; Yaacob, Siti Nor; Mohd Arif, Nur Aqilah; Sabri, Mohamad Fazli (Universiti Putra Malaysia Press, 2019)
Research on marriage, its correlates and consequences, has been mostly done in the Western countries and often the dependent variable links with the subjective evaluation on the quality of the marriage. Marital instability has been steadily included as one of the outcome variables which may imply the lack of commitment towards sustaining the relationship. Considering the increased trend in number of recorded divorce cases among the Malays in Malaysia, this study utilized Rusbult's Investment Model to examine the relationships between marital satisfaction, alternatives, investment and commitment toward marriage among married working women. The model postulates that an increases in satisfaction, decreases in quality of alternative, and increases in investment size would increase one's commitment in the marital relationship, hence, hindering marital dissolution. Using data on three hundred fifteen (n=315) married women from dual-earner couples in Malaysia, this study aims to determine the relationships between the aforementioned variables. Significant bivariate relationships between all independent variables and marital commitment were established. Findings of multiple regression analyses on the relevant variables for the model revealed that alternatives in marriage served as the strongest predictor of marital commitment, followed by marital satisfaction and marital investment. This model explained 65% of variance of marital commitment of the respondents in the study. However, controlling for selected socio-demographic variables, the findings indicated that married working women who perceived low quality of alternatives, with lower family income and higher marital satisfaction tended to have greater marital commitment. This additional analysis which explains only 45% of variance of marital commitment of the respondents also revealed that marital investment was not one of the significant predictors. Findings of the study lend support for the hypotheses derived from the model. Embracing contextual variables in the analysis explains the role of family income, and highlights variation in the role of marital investment as a predictor for marital commitment. The insignificant role of marital investment may imply that the inclination to weigh on marriage in terms of gain and lost may not be perceived as critical among the respondents. Confounding roles of cultural elements, economic interdependence and its associated variables may need to be further explored in future studies.